CHINESE EFL UNDERGRADUATES’ ACADEMIC WRITING: RHETORICAL DIFFICULTIES AND SUGGESTIONS - Bian, Xiaoyun; Wang, Xiaohong (Indonesian Journal of Applied Linguistics, 2016)
Difficulties encountered by students in L2 academic writing has been a subject of research for several decades. However, to date, there still remains a lack of detailed and in-depth investigation into this area of interest. This qualitative study thoroughly investigated the rhetorical difficulties faced by Chinese EFL undergraduate academic writers, and collected suggestions on how to address these rhetorical issues. To be sufficiently detailed and thorough, this study divided students' difficulties into process- and product-related difficulties, and used triangulated data from supervisors' perspectives, students' perspectives, and supervisors' comments to address research questions. Although there were no strong generalizations derived from data from different perspectives and sources, the findings of this study showed supervisor perceptions of the rhetorical difficulties the students experienced were almost identical. In nature these rhetorical difficulties were culturallyembedded and genre-related issues; and the degree of difficulty experienced by each student varied. In this study, supervisors and students both suggested that, to solve rhetorical difficulties, teacher student communication should be improved. This study provided empirical evidence to contrastive rhetoric theory and socio-cultural theory. It also offered suggestions on how to strengthen future research in this area of inquiry, and how to improve academic writing teaching in L2 educational contexts.